2010
DOI: 10.1002/hyp.7868
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of depth‐integrated fluxes of suspended sediment in the Amazon River: particle aggregation as a complicating factor

Abstract: International audienceLarge rivers have been previously shown to be vertically heterogeneous in terms of suspended particulate matter (SPM) concentration, as a result of sorting of suspended solids. Therefore, the spatial distribution of suspended sediments within the river section has to be known to assess the riverine sedimentary flux. Numerous studies have focused on the vertical distribution of SPM in a river channel from a theoretical or experimental perspective, but only a few were conducted so far on ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
123
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(137 citation statements)
references
References 65 publications
(71 reference statements)
13
123
0
1
Order By: Relevance
“…These results indicate that flocs of both rivers are strong flocs (low values of n), which is logical because shear rates at the Usumacinta and Grijalva rivers are high (for comparison u* at Amazon River varies between 0.07 and 0.1 [1]). It is also observed that the value of Z R in the Usumacinta river is more sensitive to changes in the value of n. It was observed that for large depths it is more difficult to define the n value as it can change even in the same cross section of the river at different levels.…”
Section: Applications In Water Systems Management and Modeling 124mentioning
confidence: 81%
See 3 more Smart Citations
“…These results indicate that flocs of both rivers are strong flocs (low values of n), which is logical because shear rates at the Usumacinta and Grijalva rivers are high (for comparison u* at Amazon River varies between 0.07 and 0.1 [1]). It is also observed that the value of Z R in the Usumacinta river is more sensitive to changes in the value of n. It was observed that for large depths it is more difficult to define the n value as it can change even in the same cross section of the river at different levels.…”
Section: Applications In Water Systems Management and Modeling 124mentioning
confidence: 81%
“…The formation of flocs in large rivers is the reason why Rouse equation cannot be used with particle sizes from classical granulometric measurements in conjunction with non-cohesive settling velocity equations. Recently, researchers working in the Amazon River and tributaries made similar observations [1]. Their conclusion was that granulometric measurements performed did not represent the real particle size because cohesive sediments agglomerate to form flocs [5,6,9] and after sampling, these flocs are destroyed and could not be measured appropriately in laboratory.…”
Section: Application To Suspended Load Estimation In Large Riversmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, interpreting point measurements at one location of the river network is limiting because large rivers systems like the Amazon are heterogeneous in space and time. Within the Amazon cross-section, hydrodynamic sorting causes large grain-size sediments to settle faster and thus concentrate at deeper depths (Rouse 1950;Gibbs, 1967;Curtis et al, 1979;Bouchez et al, 2011b), leading to compositional differences between the deeper, coarser sediments and the shallower, finer sediments (Bouchez et al, 2011a;Bouchez et al, 2014). Finally, seasonality presents another challenge to measuring fluxes.…”
Section: Introductionmentioning
confidence: 99%